Long-term periodontal status of maxillary central incisors after orthodontic traction: CBCT and clinical findings - Calil, Louise Resti (2018)
Purpose: The aim of this study was to evaluate the buccal and lingual alveolar bone morphology and the periodontal clinical condition of impacted permanent maxillary central incisors at least 6 months after the orthodontic traction. Methods: This split mouth transversal study evaluated a sample of 11 patients a mean of 15.41 years after the orthodontic traction of unilateral impacted maxillary central incisor. The experimental group (TR) consisted of 11 impacted central incisors. The comparison group (NTR) consisted of 11 non-impacted contralateral teeth. High-resolution CBCT exams of central incisors were performed using Accuitomo (J. Morita, Kyoto, Japan). Cross section imagens passing through the center of maxillary central incisors were used to measure buccal and lingual alveolar bone level. Presence of fenestration, root dilacerations, root coverage, and position of the root apex were also assessed in the same images. Clinical parameters included the periodontal probing depth, attachment level, gingival bleeding index, plaque index, degree of gingival recession, amount of gingival mucosa and evaluation of interproximal papilla and black triangle. Digital model analysis included an assessment of clinical crown height and width. Intergroup comparisons were performed using paired t tests, McNemar and Wilcoxon tests (p<0.05). Pearson correlation coefficient was calculated to determine the relationship between the clinical and CBCT findings. Results: TR group showed a significantly thinner buccal bone plate thickness at the middle and apical root level compared to NTR group. A decreased buccal alveolar crest level was observed in TR group in comparison to NTR group. The TR group showed a greater frequency of buccal bone dehicences and root dilacerations than antimeres. Experimental group showed more gingival recession, a decreased amount of gingival mucosa and an increased clinical attachment level at the buccal aspect than the NTR group. Moderate inverse correlation was found between buccal bone plate thickness of central incisors and attachment level and moderate positive correlation was found between buccal alveolar crest height and attachment level Conclusions: The periodontal conditions of maxillary central incisors long-term after orthodontic traction are different compared to its antimere. A decreased thickness and height of buccal alveolar bone and gingival recessions were observed in central incisors 15 years after orthodontic traction.